Traditional Chinese Medicine for Post-Stroke Cognitive Impairment: A Systematic Review and Meta-Analysis - Shen, Wei; Fan, Xueming; Wang, Liuding; Zhang, Yunling (Frontiers in Pharmacology, 2022)
Background: Post-stroke cognitive impairment (PSCI) affects more than one-third of stroke patients, and causes much greater harm to long-term function than the initial brain damage. No conventional Western medications have shown convincing clinical effectiveness for treating PSCI. Research shows that Traditional Chinese medicine (TCM) can improve cognitive function in patients. However, the clinical efficacy and safety remain controversial. The aim of this study was to examine the effectiveness and harmful effects of TCMs in the treatment of PSCI. Method: We searched seven databases and two clinical registration websites for randomized controlled trials (RCTs). The revised Cochrane risk of bias tool (RoB 2.0) was used to evaluate the methodological quality and RevMan 5.4 was used for data analysis. This study has been submitted to PROSPERO with registration number is CRD42020149299. Results: We included 34 studies in this review. The results of this study showed that TCM adjuvant therapy improved scores on the MoCA (MD=2.55, 95% CI [1.56, 3.53], P<0.00001; MD=3.07, 95% CI [1.98, 4.17], P<0.00001 at treatment duration of <3 and 3 months, respectively), MMSE (MD=2.55, 95% CI [1.99, 3.10], P<0.00001; MD=2.53, 95% CI [1.59, 3.47], P<0.00001; MD=2.91, 95% CI [1.26, 4.56], P=0.0006; MD=3.11, 95% CI [−0.04, 6.27], P=0.05 at treatment duration of <3, 3, 4, and 6 months, respectively), and BI (MD=7.34, 95% CI [3.83, 10.85], P<0.0001; MD=8.98, 95% CI [4.76, 13.21], P<0.0001 at treatment duration of <3 and 3 months, respectively) and reduced scores on the ADL (MD=−8.64, 95% CI [−9.83, −7.45], P<0.00001; MD=−2.00, 95% CI [−2.94, −1.06], P<0.0001 at treatment duration of 3 and 4 months, respectively), NIHSS (MD=−2.48, 95% CI [−4.97, 0.00], P=0.05; MD=−3.81, 95% CI [−6.21, −1.40], P=0.002 at treatment duration of <3 and 3 months, respectively), and CSS (MD=−2.47, 95% CI [−3.49, −1.45], P<0.00001 at a treatment duration of 3 months). No serious adverse reactions were observed. Conclusion: Despite the significant positive results, the present evidence supports, to a limited extent because of the methodological flaws and herbal heterogeneity, that TCM adjuvant therapy can be used for patients with PSCI. While, further rigorous RCTs are warranted to confirm the efficacy and safety of TCM.